Antineoplastic properties and pharmacological applications of Crotalus durissus terrificus snake venom - Alves, Brunna Fernanda Arraez; Ferreira, Rui Seabra [UNESP] (FapUNIFESP (SciELO), 2022)
Snake toxins are widely studied owing to their importance in snakebite accidents, a serious public health issue in tropical countries, and their broad therapeutic potential. Isolated fractions from venom produced by snakes of the genus Crotalus sp. present a wide variety of pharmacological uses such as antifungal, antiviral, antibacterial, and antitumor properties, among other therapeutic potentialities. Given the direct effect of this venom on tumor cells, isolation of its compounds is important for the characterization of its anticarcinogenic actions. Crotalus durissus terrificus venom and its toxins have been widely evaluated as potential candidates for the development of new antineoplastic therapies that are efficient against different tumor lines and cellular targets. This review highlights the venom toxins of this species, with a focus on their antineoplastic properties.
Keywords: Antitumor; Cancer; Crotalid Venoms; Crotalus; Snake Venom